Narrative Representation of Mental Health and Marginalization in Joker: A Cultural Literature Analysis - Jamalullail, Ali Ridho; Ahzani , Nizam (Journal Corner of Education, Linguistics, and Literature, 2025)
This study examines the narrative and cultural representation of mental health and marginalization in the 2019 film Joker through a qualitative approach. Framed as a form of visual literature, Joker offers a profound lens to explore the stigmatization of mental illness and the societal alienation faced by marginalized individuals. Utilizing narrative analysis and cultural studies, our study investigates key elements such as characterization, symbolism, and thematic structures to uncover how the film critiques societal attitudes and systemic failures related to mental health. The findings reveal that Joker humanizes its protagonist, Arthur Fleck, while exposing the broader societal and institutional mechanisms that perpetuate stigma and inequality. This study contributes to the growing body of literature on mental health and cultural studies by emphasizing the role of visual media in challenging dominant narratives and fostering critical discourse. The implications extend to fields such as literature, cultural representation, and education, advocating for the use of media as a tool for promoting mental health awareness and social inclusion.